(untitled) (Research, Society and Development, 2021)
The Pantanal constitutes the biggest floodplain of the world, forming a mosaic of different habitats, sustaining rich aquatic and terrestrial biota. This mosaic of habitats of the Pantanal is well represented in the Barão de Melgaço region by the Chacororé-Sinhá Mariana Lake System, this system of parental lakes of Cuiabá river are recognized by their aquatic productivity and scenically beauty. The aquatic macrophyte are very abundant organisms being considered the most productive community in the aquatic system, with great capacity of accumulate biomass and nutrients. The samples were collected into three stations representing the Chacororé-Sinhá Mariana lakes and the transition between them. This study had as purpose to evaluate the spatial and temporal dynamic of biomass in E. crassipes in the stands of this specie in Chacororé-Sinhá Mariana “baía” system. The results shown that both lakes shown bigger biomass during flood, and that in transition sample area were verified the bigger biomass of studied areas. This research supports another studies realized in the Pantanal about the importance of the “flood pulse” in the temporal variation of the biomass and shown that the variation of the biomass of E. crassipes in the lakes evidence the spatial heterogeneity which exists between those lakes. In this way the aquatic macrophyte can indicate the impacts resulting of the hydrological changes in this system of lakes.